Determination of Caffeic Acid in Ethanolic Extract of Spent Coffee Grounds by High-Performance Liquid Chromatography with UV Detection - Michael Raharja Gani; Enade Perdana Istyastono (Universitas Gadjah Mada, 2021)
We developed a method for determining the caffeic acid in spent coffee grounds. The spent coffee ground solution was prepared by blending 3 g spent coffee grounds with 60 mL ethanol/water (40/60 v/v) for 2 h on a hot plate magnetic stirrer (60 °C, 350 rpm). The mixture was filtered and the filtrate was concentrated under vacuum (60 °C) to 5 mL. The method employed a reversed-phase high-performance liquid chromatography with a UV detector. We used a Phenomenex Luna column (250 × 4.6 mm; i.d., 5 µm) under isocratic elution, and the mobile phase was acetonitrile-methanol-aqueous formic acid (10:10:80 v/v), with a flow rate of 0.9 mL/min. Analysis was performed at 324 nm. The column temperature was set at 27 °C temperature. The results showed that this method was selective for quantifying the caffeic acid in spent coffee grounds with good linearity in the range of 1.31–17.07 μg/mL. The detection and quantitation limits were 0.28 and 0.84 μg/mL, respectively. The mean intraday and interday recoveries were 83.80–95.17% and 82.16–97.40%, respectively. Intraday and interday precision expressed as the relative standard deviation (RSD) were below 7.3%. There was 0.17% ± 0.006 w/w caffeic acid in the spent coffee grounds (RSD = 3.63%, n = 3).